Protein-mediated anti-adhesion surface against oral bacteria. Issue 6 (26th January 2018) - Liu, Xi; Peng, Liying; Meng, Jingxin; Zhu, Zhongpeng; Han, Bing; Wang, Shutao
Abstract : Biomedical materials, such as orthopedic biomaterials, have a great impact on improving life quality and self-esteem of human beings. Abstract : Biomedical materials, such as orthopedic biomaterials, have a great impact on improving life quality and self-esteem of human beings. However, the usage of fixed appliances during dental treatment often increases the difficulty of oral cleaning and enlarges the adhesion opportunity of oral bacteria. Furthermore, the existing anti-adhesion coatings, such as polyethylene glycol derivatives and zwitterionic polymers, have not been universally accepted in the oral environment due to their intrinsic problems. Herein, inspired by the anti-adhesion capability of bovine serum albumin, we report a facile protein-based anti-bacterial surface, showing excellent anti-adhesion performance toward oral bacteria. This protein-mediated anti-adhesion strategy may provide a promising clue for developing new anti-bacterial biomaterials, such as dental fixed appliances, restorative materials and medical mouthwashes.